Gamification Approaches in Undergraduate Histology Learning: Pendekatan Gamifikasi dalam Pembelajaran Histologi pada Tingkat Sarjana - Nur Aini Hasan; Rifda Savirani (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Histology is a fundamental component of preclinical medical education that requires mastery of microscopic interpretation and integration of structure–function relationships. Specific Background: First-year medical students frequently perceive histology as challenging due to high cognitive load, abstract visual content, reliance on memorization, and limited motivation associated with conventional lecture-based teaching. Knowledge Gap: Although gamification has been increasingly applied in medical education, there remains limited synthesis focusing specifically on its application, outcomes, and limitations within undergraduate histology learning, particularly regarding standardized evaluation and long-term sustainability. Aims: This narrative literature review aims to examine the relevance of gamification in basic histology education, identify commonly used gamification tools, and summarize reported educational outcomes across undergraduate medical curricula. Results: The reviewed literature indicates that gamification strategies, including points, badges, leaderboards, interactive quizzes, and digital challenges, are associated with improved learner engagement, motivation, knowledge retention, self-confidence, and active classroom participation across cognitive, affective, and behavioral domains. Novelty: This review consolidates evidence on gamification specifically within histology education while simultaneously highlighting methodological limitations, novelty effects, competitive risks, and design heterogeneity reported in existing studies. Implications: Carefully designed, theory-driven, and context-adapted gamification frameworks, integrated with digital microscopy and evaluated through longitudinal research, may support more interactive and meaningful histology learning experiences for early-stage medical students. Highlights: Interactive game-based strategies are consistently associated with higher learner participation and motivation in microscopic science learning. Reported outcomes span cognitive, affective, and behavioral domains, including retention, satisfaction, and active learning behaviors. Design variability and limited long-term evaluation remain key challenges in current implementations. Keywords : Gamification, Histology Education, Medical Students, Engagement, Preclinical Learning